PENGARUH EDUKASI PENDIDIKAN MELALUI MEDIA VIDIO ANIMASI TERHADAP KETERAMPILAN MENYIKAT GIGI YANG BAIK DAN BENAR DI SDN 2 KABUPATEN BENER MERIAH - Lisa Amanda; Zulfikar; Nurlaely HS (LLDIKTI WILAYAH XIII, 2025)
Problems that cause disturbance health tooth And mouth between other like tooth cavitie, caries on toothache, inflammation on gums, as well as infections others. Research This done with objective For to find out the influence of educational media through animated videos on good and correct tooth brushing skills. The research design used was pre-experimental one group pretest-posttest design. Population in study This is all over student classes IV to VI as many as 79 people. Sample obtained with technique random sampling formula of 66 respondents. Based on statistical analysis using the Wilcoxon test, the p value ( 0.000) < α (0.05) was obtained, so Ha was accepted and Ho was rejected. Thus, it can be concluded that there is an influence of education . education via video media animation to skills brushing teeth. Research This it is hoped that students apply skills brushing your teeth properly and correctly. Keywords: Education, Video Mediaskills Brushing Teeth What Is Good And Correct